Palm oil biomass for electricity generation in Malaysia - N. A., Ludin; M. A., M. Bakri; M., Hashim; B., Sawilla; Menon, N. R., Ir.; H., Mokhtar (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/